Effects of Passive Movement on Motor Function and Disability in Patients with Stroke: A Systematic Review and Meta-Analysis - Auwal Abdullahi; Thomson W. L. Wong; Shamay S. M. Ng (Journal of Functional Morphology and Kinesiology)
Background: Severe impairment in motor function following a stroke can pose a significant challenge during rehabilitation since the patients are unable to carry out active forms of rehabilitation, such as task-specific training. Thus, in such a case, passive movement can be utilized. The aim of this systematic review and meta-analysis is to determine from the literature the evidence on the effects of passive movement compared with a control on recovery outcomes post stroke. Method: Four databases, PubMED, Embase, Web of Science (WoS), and CENTRAL, were searched. Data on the study participants’ characteristics, such as the mean age, the mean time since stroke, the protocol of the experimental and control interventions, the mean scores on the outcomes assessed post intervention and at follow-up, and the number of participants in both the experimental and control groups were extracted. Result: Four studies (n = 166), with two having a moderate quality and two having a high methodological quality, were included in the study. The test for overall effects showed that passive movement is superior to the control at improving the recovery of function (SMD = 0.82, 95% CI = 0.40 to −1.24, p = 0.0002) post intervention. However, the results of the individual domains showed that the experimental group is only superior to the control at improving motor function (SMD = 0.70, 95% CI = 0.21 to 1.18, p = 0.005) and disability (SMD = 0.81, 95% CI = 0.32 to 1.31, p = 0.001). Conclusions: Evidence for the effects of passive movement on recovery outcomes in patients with stroke seems to be low. Therefore, the clinical decision on its application requires reflection, and further randomized controlled trials need to be carried out to determine the evidence.